Conhecimento e associação com o etilismo na hipertensão arterial - Torres, Débora Dada Martineli (2015)
Introduction: Chronic diseases are health problems that persist over time and require constant care and changes in lifestyle. The main chronic diseases is high blood pressure. Alcohol consumption is considered a risk factor for high blood pressure in low doses has shown a cardiovascular benefit. Objectives: analyze the hypertensive and normotensive population, as the knowledge of hypertension, the concept of health, the measurement of PA; and evaluate the association between alcohol consumption and high blood pressure in the adult population of Sao Jose do Rio Preto / SP. Methods: Cross-sectional study in a sample of 1,717 individuals (hypertensive and normotensive) stratified by age group representative of the adult population (≥ 18 years) and urban city of São Jose do Rio Preto / São Paulo, Brazil. The participants answered a semi-structured interview with sociodemographic data, education, blood pressure control, aware of being hypertensive, health concept, monitoring of blood pressure and alcohol consumption. Statistical analysis was done through the Minitab software version 12.22, Maple 9:03, R 2.4.1, using the following statistical tests: Student t test, chi-square test or Fischer's exact test and the significance level adopted was p <0.05. Results: Of 762 classified as hypertensive, aged 18-39 years old, 33% were unaware of hypertension, and the knowledge increased with advancing age. The concept of health there was a decrease in good / excellent responses in young for regular / bad the elderly, most hypertensive reported that would monitor blood pressure, the last blood pressure measurement was less than a month. The study showed association of alcohol consumption and high blood pressure in the adult population analyzed, and the individuals who reported consuming more alcohol were male, with low education level and belonging to lower social classes. It showed cardiovascular protection in individuals who consume alcohol moderately (p = 0.035). Conclusion: These data refer to the population of São José do Rio Preto and reinforce the need to implement health interventions, promoting the knowledge of their health condition, improving the quality of life and thus reducing the rates of morbidity and mortality.